Thermal performance of fired and unfired earth bricks walls. (March 2020) - Bruno, Agostino Walter; Gallipoli, Domenico; Perlot, Céline; Kallel, Hatem
Abstract: The paper presents the results from a series of thermal tests on five wall samples made of four types of unfired and one type of fired earth bricks. The unfired earth bricks were manufactured in the present work and consisted of Proctor compacted full bricks, hypercompacted full bricks, hypercompacted full bricks with hemp fibres and hypercompacted hollow bricks. Instead, the fired earth bricks were standard full bricks purchased from a provider of building materials. The walls were laid by using a fine earth mortar in the case of the unfired bricks and a standard cement mortar in the case of the fired bricks. The walls were tested inside a double-room climatic chamber where they were subjected to different temperatures on their two faces reproducing typical indoor and outdoor conditions. The thermal efficiency of the walls was assessed by quantifying the heat exchanged between the indoor and outdoor environments under both winter and summer testing conditions. The best thermal efficiency was observed for the unfired hypercompacted hollow brick wall while the worst efficiency was observed for the unfired hypercompacted and fired full bricks walls. An intermediate efficiency was recorded for the walls made of unfired full bricks either lightly compacted or hypercompacted with hemp fibres. The results from the present campaign provide an experimental database for the validation of heat transfer models at structural scale, thus contributing to the promotion of raw earth as a sustainable construction material.